Analysis of Occupational Safety and Health Risk Using the HAZOPS Method and ergonomics Approach (RULA and REBA) at UD. Sekar Surabaya - Tyas Septia Nova; NI Luh Putu Hariastuti (Jurnal SENOPATI : Sustainability, Ergonomics, Optimization, and Application of Industrial Engineering, 2022)
UD. Sekar Surabaya is a small and medium enterprise, which produces uyel crackers. In the development of cracker production activities, of course there is a production process that is dangerous (hazard). If not controlled this potential hazard can cause various problems, such as fatigue, musculoskeletal complaints, the risk of injury, and the most serious work accidents. The purpose of this research is to help UD. Sekar Surabaya identifies hazards in the production process to control and prevent potential hazards in the work area. To find out the ergonomic hazards, the HAZOPS method was used for identification, then followed by the NMB questionnaire to determine the part of the worker's body that felt pain. Then use the RULA and REBA methods to calculate body posture, where the results of these calculations will be used as suggestions for improvement to reduce the risk of work accidents. From the results of the hazard analysis, it can be seen that the hazards that can cause work accidents are attitudes and the physical work environment. In addition, there are ergonomic risks in the cracker production process. The risks experienced by workers are musculoskeletal complaints and pain in the neck, shoulders, arms, back, hands and feet. The recommended stations for improvement are the process of taking flour from the warehouse, the process of inserting the rack into the oven, the process of lifting the ducks to the drying station, and the process of frying crackers.